Analysis of Employee Competency Development - Setiawan, Irfan (Institut Pemerintahan Dalam Negeri, 2023)
AThis research aims to examine the analysis of the competency development of the State Civil Officials in Tangerang Regency. This study uses a descriptive qualitative research method with an inductive approach. Primary data collection comes from observations and interviews with informants, namely employees who have the authority and duties in developing the competence of Officialsin Tangerang Regency, and Secondary Data obtained from documents at the Tangerang Regency Personnel and Human Resources Development Agency. Researchers used the data analysis technique of the Miles & Huberman model. Competency development carried out by the Tangerang Regency Personnel and Human Resource Development Agency has not been running effectively due to a lack of cooperation built by the Tangerang Regency Personnel and Human Resource Development Agency, the implementation of the Training Needs Analysis has not been maximized, the ineffectiveness of the implementation of education and training, there is still political intervention in the implementation of transfer, as well as the lack of motivation for civil servants in Tangerang Regency. So that the Personnel and Human Resources Development Agency for Tangerang Regency needs to build cooperation by conducting information dissemination and field visits related to the conditions for developing civil servant competencies, maximizing the SIMPEG and SIDAK applications to streamline the implementation of Training Needs Analysis, increasing supervision in organizing training and carrying out transfer management based on the principle put the right people in the right places.